2013
DOI: 10.1016/j.profoo.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutrient Levels for Three Fresh Pork Loin Cuts between 1992 and 2010

Abstract: Since nutrient composition of pork has changed over the past two decades, a collaborative study was conducted by scientists at the US Department of Agriculture (USDA), Texas Tech University and the National Pork Board to determine current nutrient values. The purpose was to obtain analytical nutrient data for three highly consumed fresh pork products in the USDA National Nutrient Database for Standard Reference (SR) and to compare the results to data obtained in 1992. Bone-in baby back ribs (BKR), boneless sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…There have been many changes to the production of pork, including different breeds of pigs, a change in diet and an increase in supplementation and these changes will have impacted the fat content. Others have also noted a decrease in fat content (Williams et al 2013) and the results from this survey are similar to that found in Australia (Greenfield et al 2009).…”
Section: Resultssupporting
confidence: 89%
“…There have been many changes to the production of pork, including different breeds of pigs, a change in diet and an increase in supplementation and these changes will have impacted the fat content. Others have also noted a decrease in fat content (Williams et al 2013) and the results from this survey are similar to that found in Australia (Greenfield et al 2009).…”
Section: Resultssupporting
confidence: 89%